Exploring taxonomic and functional microbiome of Hawaiian stream and spring irrigation water systems using Illumina and Oxford Nanopore sequencing platforms - Klair, Diksha; Dobhal, Shefali; Ahmad, Amjad; Hassan, Zohaib Ul; Uyeda, Jensen; Silva, Joshua; Wang, Koon-Hui; Kim, Seil; Alvarez, Anne M.; Arif, Mohammad (Frontiers in Microbiology, 2023)
Irrigation water is a common source of contamination that carries plant and foodborne human pathogens and provides a niche for proliferation and survival of microbes in agricultural settings. Bacterial communities and their functions in irrigation water were investigated by analyzing samples from wetland taro farms on Oahu, Hawai’i using different DNA sequencing platforms. Irrigation water samples (stream, spring, and storage tank water) were collected from North, East, and West sides of Oahu and subjected to high quality DNA isolation, library preparation and sequencing of the V3-V4 region, full length 16S rRNA, and shotgun metagenome sequencing using Illumina iSeq100, Oxford Nanopore MinION and Illumina NovaSeq, respectively. Illumina reads provided the most comprehensive taxonomic classification at the phylum level where Proteobacteria was identified as the most abundant phylum in the stream source and associated water samples from wetland taro fields. Cyanobacteria was also a dominant phylum in samples from tank and spring water, whereas Bacteroidetes were most abundant in wetland taro fields irrigated with spring water. However, over 50% of the valid short amplicon reads remained unclassified and inconclusive at the species level. In contrast, Oxford Nanopore MinION was a better choice for microbe classification at the genus and species levels as indicated by samples sequenced for full length 16S rRNA. No reliable taxonomic classification results were obtained while using shotgun metagenome data. In functional analyses, only 12% of the genes were shared by two consortia and 95 antibiotic resistant genes (ARGs) were detected with variable relative abundance. Full descriptions of microbial communities and their functions are essential for the development of better water management strategies aimed to produce safer fresh produce and to protect plant, animal, human and environmental health. Quantitative comparisons illustrated the importance of selecting the appropriate analytical method depending on the level of taxonomic delineation sought in each microbiome.